Noise legitimacy in public libraries in Malaysia - Kat, Mui Yen (Kulliyyah of Information Communication and Technology, International Islamic University Malaysia, 2017)
The purpose of this study is to discuss the suitable new user-friendly learning environment to support current users' learning trend in public libraries in Malaysia in order to change the service image of libraries. Libraries not only have served as silent and serious reading centers but also as learning center to support different types of users' learning trends. The objective of this research is to investigate and identify the present condition of learning, suitable noise levels and preferred library set up among the users of public library in Malaysia. The study was conducted to compare and evaluate the learning ability in reading at different background discourse noise levels, <45dB, <50dB, and <55dB and the users' preference library set up in public library in Malaysia. The hypotheses were tested by using pair samples; t-test, one way ANOVA, and two-way repeated ANOVA were performed on data collected from 315 teenager users aged ranged between 13 to 19 years old from Perbadanan Perpustakaan Awam Johor branch in Segamat. SPSS was used to generate results for all independent and dependent variables. The quantitative research as a true experimental research was used in collecting the numerical data. Simple random sampling was done in the data collection process. The samples were measured into two different situation, control and experimental. The two measurements were from the score obtained from learning ability in reading at different noise levels. The results showed that there is a significant relationship between learning ability in reading and noise levels. Noise levels at the range of <45dB were found no significant effect on the users' learning ability in reading. The users' preference library set up are still the traditional type and the users' preference library set up was found no significant effect on the users' learning ability in reading across to the different noise levels. This research has several practical applications. Firstly, these finding suggest that the noise levels at the range of <45dB are suitable to be allowed in public libraries in Malaysia. Secondly, it provides thoughtful evidence to library professionals in Malaysia to expand their understanding in dealing with noise issues. Lastly, the implication of the research for public libraries in Malaysia and the need for further researches in the field were discussed.